A new genus of the family Portunidae (Crustacea: Decapoda: Brachyura) and the identity of Portunus (Cycloachelous) yoronensis Sakai, 1974 - Nguyen, T. S.; Ng, Peter K. L. (Zootaxa, 2010)
A new genus is established for Neptunus (Achelous) dubia Laurie, 1906, a species that ranges from the eastern Indian Ocean to the Philippines and French Polynesia. This species is probably closest to Cycloachelous Ward, 1942, with regard to the carapace shape and form of the chelipeds, but has a very unique adult male sternal medial groove with two prominent deep depressions on sternite 8 in the sterno-abdominal cavity to accommodate distinctive male first gonopods, that differs from all known portunid genera. Portunus (Cycloachelous) yoronensis Sakai, 1974, described from Japan, is confirmed to be a junior synonym of N. (A.) dubia Laurie, 1906.